Pulmonary cytomegalovirus (CMV) DNA shedding in allogeneic hematopoietic stem cell transplant recipients: Implications for the diagnosis of CMV pneumonia - Piñana, José Luis (J Infect, 2019)
OBJECTIVES: To date no definitive cut-off value for cytomegalovirus (CMV) DNA load in bronchoalveolar lavage (BAL) fluid specimens has been established to discriminate between CMV pneumonia and pulmonary CMV DNA shedding in allogeneic hematopoietic stem cell transplant (allo-HSCT) recipients. METHODS: The current retrospective study is aimed at assessing the range of CMV DNA loads quantified in BAL fluid specimens from allo-HSCT patients with pneumonia in which different microorganisms were causally involved. RESULTS: A total of 144 BAL specimens from 123 patients were included. CMV DNA was detected in 56 out of 144 BAL fluid specimens and the median CMV DNA load from patients in whom CMV pneumonia was unlikely or could be tentatively ruled out was 1210 (31–68, 920) IU/ml. The frequency of CMV DNA detection and median CMV DNA loads were comparable, irrespective of the attributable cause of pneumonia. Detection of CMV DNA loads in BAL fluid specimens >500 IU/ml was independently associated with pneumonia-attributable mortality. CONCLUSIONS: The current study highlights the difficulty in establishing universal CMV DNA load thresholds in BAL fluid specimens for distinguishing between CMV pneumonia and pulmonary CMV DNA shedding, and suggests that the presence of CMV DNA in BAL fluid specimens beyond a certain level may have a deleterious impact on patient outcome.